2010
DOI: 10.1007/s10545-010-9127-1
|View full text |Cite
|
Sign up to set email alerts
|

Complete deficiency of methylenetetrahydrofolate reductase in mice is associated with impaired retinal function and variable mortality, hematological profiles, and reproductive outcomes

Abstract: Severe deficiency of methylenetetrahydrofolate reductase (MTHFR) with homocystinuria can result in early demise or later-onset neurological impairment, including developmental delay, motor dysfunction, and seizures. We previously characterized BALB/c Mthfr (-/-)mice as a model for this disorder and have recently backcrossed the disrupted allele onto the C57Bl/6 background to examine the variable phenotypes in MTHFR deficiency. Compared with BALB/c Mthfr (-/-)mice, C57Bl/6 Mthfr (-/-)mice have enhanced survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…To that end, we comparatively analyzed regional brain homogenates from 22-month-old wt and het Mthfr mice fed an amino acid defined diet with normal folate content (normal folate diet, NF). Null Mthfr −/− mice could not be used in these studies, since mice with severe MTHFR deficiency die prematurely as a result of atherosclerosis and other complications (Chen et al, 2001; Lawrance et al, 2011). Similar to the effects of MTHFR deficiency in young Mthfr +/− mice (Figure 2), plasma tHcy levels were increased by an average of ~1.6-fold in old Mthfr +/− mice, relative to wt controls (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…To that end, we comparatively analyzed regional brain homogenates from 22-month-old wt and het Mthfr mice fed an amino acid defined diet with normal folate content (normal folate diet, NF). Null Mthfr −/− mice could not be used in these studies, since mice with severe MTHFR deficiency die prematurely as a result of atherosclerosis and other complications (Chen et al, 2001; Lawrance et al, 2011). Similar to the effects of MTHFR deficiency in young Mthfr +/− mice (Figure 2), plasma tHcy levels were increased by an average of ~1.6-fold in old Mthfr +/− mice, relative to wt controls (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, although retinopathy has been shown in a mouse model (Lawrance et al 2011) and eye involvement is frequent in other methylation disorders such as the cblC, cblE and cblG defect (Fischer et al 2014;Huemer et al 2014a, b), eye disease has rarely been reported in severe MTHFR deficiency (Ronge and Kjellman 1996). This study indicates that patients with severe MTHFR deficiency should regularly be monitored for eye disease since nystagmus, visual impairment and optic atrophy were present in this cohort in 18 % of cases and symptoms were considered burdensome in 50 % of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mice deficient in (or lacking) the enzyme methylene tetrahydrofolate reductase (MTHFR), which converts N 5 ,N 10 -methylenetetrahydrofolate into N 5 -methyltetrahydrofolate, the predominant circulating form of folate in the body, have high levels of homocysteine but no defect in the transsulfuration pathway. 41 These mice offer a handsome alternative tool for examining the consequences of excess homocysteine in the retina. With these mice in hand, we should be poised to dissect the role of hyperhomocysteinemia in retinal structure and function; studies are now under way to investigate this systematically.…”
Section: Discussionmentioning
confidence: 99%